Dual Role of Probiotic Lactic Acid Bacteria Cultures for Fermentation and Control Pathogenic Bacteria in Fruit-Enriched Fermented Milk - Borgonovi, Taís Fernanda [UNESP]; Fugaban, Joanna Ivy Irorita; Bucheli, Jorge Enrique Vazquez; Casarotti, Sabrina Neves; Holzapfel, Wilhelm Heinrich; Todorov, Svetoslav Dimitrov; Penna, Ana Lucia Barretto [UNESP] (Springer Nature, 2024)
The food industry has been developing new products with health benefits, extended shelf life, and without chemical preservation. Bacteriocin-producing lactic acid bacteria (LAB) strains have been evaluated for food fermentation to prevent contamination and increase shelf life. In this study, potentially probiotic LAB strains, Lactiplantibacillus (Lb.) plantarum ST8Sh, Lacticaseibacillus (Lb.) casei SJRP38, and commercial starter Streptococcus (St.) thermophilus ST080, were evaluated for their production of antimicrobial compounds, lactic acid and enzyme production, carbohydrate assimilation, and susceptibility to antibiotics. The characterization of antimicrobial compounds, the proteolytic activity, and its inhibitory property against Listeria (List.) monocytogenes and Staphylococcus (Staph.) spp. was evaluated in buriti and passion fruit-supplemented fermented milk formulations (FMF) produced with LAB strains. Lb. plantarum ST8Sh was found to inhibit List. monocytogenes through bacteriocin production and produced both L(+) and D(−) lactic acid isomers, while Lb. casei SJRP38 mainly produced L(+) lactic acid. The carbohydrate assimilation profiles were compatible with those usually found in LAB. The potentially probiotic strains were susceptible to streptomycin and tobramycin, while Lb. plantarum ST8Sh was also susceptible to ciprofloxacin. All FMF produced high amounts of L(+) lactic acid and the viability of total lactobacilli remained higher than 8.5 log CFU/mL during monitored storage period. Staph. aureus ATCC 43300 in fermented milk with passion fruit pulp (FMFP) and fermented milk with buriti pulp (FMB), and Staph. epidermidis KACC 13234 in all formulations were completely inhibited after 14 days of storage. The combination of Lb. plantarum ST8Sh and Lb. casei SJRP38 and fruit pulps can provide increased safety and shelf-life for fermented products, and natural food preservation meets the trends of the food market.
Keywords: Antimicrobial compounds; Fermented milk; Food safety; Pathogenic bacteria